IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA PROGRAM KETAHANAN PANGAN DI DESA SIMPANG HARAPAN - Haidir Ali; Arrafiqur Rahman; Seprini (Journals of Indonesian Multidisciplinary Research, 2026)
This research aims to analyze the implementation of human resource (HR) management, identify supporting and inhibiting factors, and analyze the role of HR management in the effectiveness of the food security program in Simpang Harapan Village. The phenomenon shows that while 20% of the Village Fund has been allocated, the program's effectiveness heavily relies on the capacity of local HR to manage agricultural potential holistically. This study employed a qualitative descriptive approach. Data were collected through non-participatory observation, in-depth interviews with 15-23 informants (key, primary, and supporting informants), and documentation. The data analysis technique followed the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing/verification. The results of the study indicate that: (1) The implementation of HR management in Simpang Harapan Village encompasses participatory planning, implementation through routine technical guidance, and periodic supervision; however, it remains largely administrative and has not yet been based on a formal performance-based system. (2) Supporting factors include strong social capital (community cooperation) and budget certainty from the Village Fund, while inhibiting factors include low technological literacy, limited infrastructure, and fluctuations in HR motivation. (3) HR management plays a determinant role in program effectiveness, where organized HR management has been proven to increase agricultural productivity and family food stability. This study concludes that HR capacity building is the primary differentiator between the success and failure of food security programs at the village level.